Qianyang Yuyin Granules for vascular damage in mild-to-moderate hypertensive patients: a systematic review with meta-analysis and trial sequential analysis - Zhu, Shidian; Wu, Qiannong; Liu, Yanlin; Liu, Fuming (Frontiers in Pharmacology, 2025)
ObjectiveThe purpose is to evaluate the clinical efficacy and safety of Qianyang Yuyin Granules in the treatment of vascular damage in essential hypertension systematically.MethodsRelevant literature databases include CNKI, Wanfang Data, VIP, CBM, PubMed, Web of Science, Cochrane Library. DeepSeek-V3 was used for AI-assisted retrieval. The time limit for searching was from the establishment of the database to 15 April 2025. Eligible randomized controlled clinical trials were screened according to inclusion and exclusion criteria. Publication bias assessment and quality evaluations were analysed by using the Cochrane Handbook and meta-analysis was performed by using RevMan 5.3 software. Finally, using Trial Sequential Analysis 0.9Beta software to perform the trial sequential analysis.Results21 studies were finally included, with a total sample of 1,419 cases, 728 cases in the experimental group and 691 cases in the control group. Meta-analysis suggested that the trial group using Qianyang Yuyin Granules was effective in lowering PWV-BS [MD = −0.58, 95%CI: (−0.88, −0.29), P < 0.0001], PWV-ES [MD = −0.79, 95%CI: (−1.22, −0.36), P = 0.0003] in the elderly population with essential hypertension (≥60 years old), lowering inflammatory factor-related indexes including CRP [SMD = −0.37, 95%CI: (−0.58, −0.16), P = 0.0005] and TNF-α [SMD = −0.44, 95%CI: (−0.70, −0.18), P = 0.001], lowering systolic blood pressure [MD = −3.86, 95%CI: (−5.33, −2.39), P < 0.00001] and diastolic blood pressure [MD = −2.24, 95%CI: (−3.39, −1.10), P = 0.0001] were all superior to the control group that only used basic treatment and the differences were statistically significant; The incidence rate of adverse reactions in the experimental group was not statistically significant when compared with that of the control group [OR = 0.71, 95%CI: (0.26, 1.93), P = 0.51]. The sequential analysis further suggested that the addition of Qianyang Yuyin Granules to reduce PWV and CRP in peripheral blood had a precise role.ConclusionThe addition of Qianyang Yuyin Granules in the treatment of vascular damage in mild-to-moderate essential hypertension can improve the clinical efficacy without increasing the adverse effects of conventional drugs, and has further clinical application value. However, further research with larger scale and stricter quality control is needed.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025641482.